2012
DOI: 10.3348/kjr.2012.13.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Renal Tumors: Four-Year Follow-Up Results in 47 Patients

Abstract: ObjectiveTo retrospectively evaluate the intermediate results of radiofrequency ablation (RFA) of small renal masses (SRMs).Materials and MethodsPercutaneous or laparoscopic RFA was performed on 48 renal tumors in 47 patients. The follow-up studies included a physical examination, chest radiography, creatinine level, and contrast-enhanced CT or MRI. To confirm the pathologic criteria of complete ablation, 35 patients underwent a follow-up biopsy. Recurrence was defined as contrast enhancement on imaging studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Nevertheless, the contribution of a confirmatory post-RFA biopsy to the diagnosis of the reccurrence can not be ignored in patients with suspected findings of recurrence on radiological analyses. In our follow up protocol including 3 rd and 6 th month controls, it was seen that no tumor (0%) reccurrences occurred, and this result was also in correlation with the literature (Gervais et al, 2005;Park et al, 2006;Zagoria et al, 2007;Ferakis et al, 2010;del Cura et al, 2010;Kim 2012). Although RFA is a less invasive treatment than surgical treatment options, various complications, such as pain, bleeding, hematuria, infection, urinary fistula, damage of adjacent structures can be occurred in RFA (Aron and Gill, 2005;Kwan and Matsumoto, 2007;Park et al, 2009;Ji et al, 2011;Atwell et al, 2012).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Nevertheless, the contribution of a confirmatory post-RFA biopsy to the diagnosis of the reccurrence can not be ignored in patients with suspected findings of recurrence on radiological analyses. In our follow up protocol including 3 rd and 6 th month controls, it was seen that no tumor (0%) reccurrences occurred, and this result was also in correlation with the literature (Gervais et al, 2005;Park et al, 2006;Zagoria et al, 2007;Ferakis et al, 2010;del Cura et al, 2010;Kim 2012). Although RFA is a less invasive treatment than surgical treatment options, various complications, such as pain, bleeding, hematuria, infection, urinary fistula, damage of adjacent structures can be occurred in RFA (Aron and Gill, 2005;Kwan and Matsumoto, 2007;Park et al, 2009;Ji et al, 2011;Atwell et al, 2012).…”
Section: Resultssupporting
confidence: 77%
“…It has been reported that different locations of the tumors could affect the complete ablation rates at initial RFA. Because some tumor locations, such as medial localization, adjacence to the vessels and other abdominal structures, and intraparanchimally localization, can make the clearly demonstration of the tumor, appropriately placement of RFA needle inside the tumor and sufficiently ablation of all parts of the tumor difficult (Gervais et al, 2005;Chen et al, 2009;Kim et al, 2012;Iannuccilli et al, 2012). In our study, there were 2 (16.6%) upper, 5 (41.6%) mid and 5 (41.6%) lower pole tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramirez et al [14] recently reported on 61 patients with RCC treated by LRFA, with a median follow-up of 59 months, the 5-year recurrence-free survival was 92%, the 5-year CSS and 5-year OS were 100 and 72%, respectively. Kim et al [11] reported on 12 patients who underwent LRFA with an 8.3% local recurrence rate at a median follow-up of 50 months.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) has been increasingly accepted in management of SRMs for its short learning curves, minimal invasiveness, and low complication rates [9]. The number of institutes performing renal tumor ablation has been increased, with encouraging functional and oncological results [10,11,12,13]. A majority of reports are on percutaneous RFA but laparoscopic RFA (LRFA) has also been reported.…”
Section: Introductionmentioning
confidence: 99%